SYNTHESIS OF WATER-SOLUBLE PHTHALOCYANIN COPPER AND COBALT BASED ON MULTI-CORE AROMATIC ACID (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The article outlines ways to synthesize the water-soluble catalyst carboxilkoboltcyaninusing mellytic acid derived from brown coal deposits in Kyrgyzstan.
Keywords: brown coal, catalyst, mellytic acid, phthalocyanins, structures, synthesis, carboxilcobaltcyanin, tetraimide, diimid, tetranitrill.